Radionuclide contamination and remediation through plants - Walther, Clemens; Gupta, Dharmendra Kumar (Springer International Publishing, 2014)
This book focuses on the mechanistic (microscopic) understanding of radionuclide uptake by plants in contaminated soils and potential use of phytoremediation. The key features concern radionuclide toxicity in plants, how the radioactive materials are absorbed by plants, and how the plants cope with the toxic responses. The respective chapters examine soil classification, natural plant selection, speciation of actinides, kinetic modeling, and case studies on cesium uptake after radiation accidents. Radionuclide contaminants pose serious problems for biological systems, due to their chemical toxicity and radiological effects. The processes by which radionuclides can be incorporated into vegetation can either originate from activity interception by external plant surfaces (either directly from the atmosphere or from resuspended material), or through uptake of radionuclides via the root system. Subsequent transfer of toxic elements to the human food chain is a concrete danger. Therefore, the molecular mechanisms and genetic basis of transport into and within plants needs to be understood for two reasons: The effectiveness of radionuclide uptake into crop plants - so-called transfer coefficient - is a prerequisite for the calculation of dose due to the food path. On the other hand, efficient radionuclide transfer into plants can be made use of for decontamination of land - so-called phytoremediation, the direct use of living, green plants for in situ removal of pollutants from the environment or to reduce their concentrations to harmless levels.